2018
DOI: 10.3390/v10090507
|View full text |Cite
|
Sign up to set email alerts
|

Caerin1.1 Suppresses the Growth of Porcine Epidemic Diarrhea Virus In Vitro via Direct Binding to the Virus

Abstract: Porcine epidemic diarrhea (PED) has re-emerged in recent years and has already caused huge economic losses to the porcine industry all over the world. Therefore, it is urgent for us to find out efficient ways to prevent and control this disease. In this study, the antiviral activity of a cationic amphibian antimicrobial peptide Caerin1.1 against porcine epidemic diarrhea virus (PEDV) was evaluated by an in vitro system using Vero cells. We found that even at a very low concentration, Caerin1.1 has the ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…The five antimicrobial peptides used in this study have been reported to inhibit the growth of various kinds of viruses including HIV, HSV-1, HSV-2, etc. [1215, 2022]. However there has been limited information about the inhibitory activity of these peptides against the swine-origin viruses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The five antimicrobial peptides used in this study have been reported to inhibit the growth of various kinds of viruses including HIV, HSV-1, HSV-2, etc. [1215, 2022]. However there has been limited information about the inhibitory activity of these peptides against the swine-origin viruses.…”
Section: Discussionmentioning
confidence: 99%
“…In one of our recently published papers, we described the antiviral activity of caerin against porcine epidemic diarrhea virus (PEDV) in vitro [20]. In this study, we investigated the activity of five AMPs including piscidin, caerin, maculatin, lactoferricin B, and indolicidin against several porcine-origin viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Brucella abortus was grown in Tryptic Soy Broth (TSB) or Tryptic Soy Agar (TSA) medium (Difco Laboratories, Detroit, MI, USA) at 37 °C. The Vero cells infected with PEDV strains were cultured in DMEM (Gibco, Langley, VA, USA) supplemented with 10 μg/mL trypsin (Gibco, Langley, VA, USA) [ 20 ]. The pVE5523 and pET28a (+) plasmids were expression vectors of Lactobacillus casei and Escherichia coli , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Guo et al revealed that caerin 1.1 shows low cytotoxicity and exhibits excellent anti-PEDV activity in a dose-dependent manner even at low concentrations (2.5, 5, 10, and 20 µg/mL). The study indicated that caerin 1.1 suppresses the growth of PEDV in vitro via direct binding to the viruses, destroys the structure of viral particles, and decreases the titers of viruses almost up to 3 logs [ 60 ]. In addition, caerin 1.1 also blocks the release of PEDV particles during virus replication to control the infection process, thus reducing the transmission of virus between neighboring cells [ 60 ].…”
Section: Antimicrobial Peptides Used Against Viruses In Swinementioning
confidence: 99%
“…The study indicated that caerin 1.1 suppresses the growth of PEDV in vitro via direct binding to the viruses, destroys the structure of viral particles, and decreases the titers of viruses almost up to 3 logs [ 60 ]. In addition, caerin 1.1 also blocks the release of PEDV particles during virus replication to control the infection process, thus reducing the transmission of virus between neighboring cells [ 60 ]. Hu et al showed that caerin 1.1 has a potent anti-PEDV activity that resulted in the residual infectivity being 0.2% in the TCID50 assay [ 40 ].…”
Section: Antimicrobial Peptides Used Against Viruses In Swinementioning
confidence: 99%